Analisis Kebijakan Guru PAI dalam Proses Pembelajaran Pendidikan Agama Islam Terhadap Siswa Inklusi dan Siswa Reguler di SMA Muhammadiyah 6 Surakarta - Wardani, Risma; Jinan, Mutohharun (TARBAWY: Indonesian Journal of Islamic Education, 2024)
This research was motivated by observations which showed that the learning process carried out by PAI teachers in the learning process was less than optimal, especially in inclusive schools so that educational goals were difficult to achieve. This has a big impact on inclusion students and regular students so that the implementation of learning is not optimal and less effective. The aim of this research is to analyze the Islamic Religious Education learning process and its implications for inclusion students and regular students. This study uses a qualitative method. Qualitative analysis is taken from PAI teachers’ interpretation of data by providing information and explanations. Research data collection was carried out using interview techniques and field observations. The results of this research show that the relationship between policy and teacher professionalism in teaching greatly influences the continuity of learning so that it can provide changes in the implementation of learning and have an impact on students in inclusive schools. Teacher policies and professionalism have a high influence on the quality of learning and student development.